FRANCISCO FREIRE ALLEMÃO DE CYSNEIROS FOR THE ARCHIVO MEDICO BRASILEIRO DE MEDICINA, CIRURGIA E SCIENCIAS ACCESSORIAS, 1845 (THE CASE OF PÁO PEREIRA) - Silva, Joelmir Marques da; Lima Filho, Amaro Bezerra de; Ferreira, Demetrius Rodrigues de Freitas (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2016)
This paper gives publicity to the article written by the physician and naturalist Francisco Freire Allemão de Cysneiros - present in Tomo II of the Archivo Medico Brasileiro de Medicina, Cirurgia e Sciencias Accessorias de 1845 -, referring to a research carried out with the Geissospermum vellosii (pau-pereira). In the study, Freire Allemão talks about the medical potentiality, the phytochemical components, the geographical distribution, as well as the taxonomic classification and morphological description of the species. The document is rare in nature, with only one copy available in the National Library Foundation and it is something of great importance regarding research on the history of science and health.